Middle/High School Algebra, Geometry, and Statistics (AGS) 4.4 Factorization of any Quadratic Polynomial - II

Example:
Factorize, 3x^{2}-11x+6.

Solution:
Given that, 3x^{2}-11x+6.
Here x^{2 }coefficient is 3 and constant term is 6
Their product is = 3 * 6 = 18
-11 = -9-2 = -9 * -2 = 18
Therefore, 3x^{2}-11x+6 = (3x^{2}-9x)-(2x-6)
Take 3x and 2 as common we get,
= 3x(x-3)-2(x-3)
Take (x-3) as common we get,
= (3x-2)(x-3)

Directions: Solve the following problems. Also write at least ten examples of your own.